ANALYSIS OF FEASIBILITY FACTORS FOR LIVABLE BEACH HOUSES, SANITATION, AND BUSINESS INTEGRATION FOR THE COMMUNITY OF KAMPUNG LAUT WAGOM DISTRICT, FAKFAK DISTRICT - Dikson Iha; Angky Soedrijanto; Sri Rahayu; Untung Tamsil (Sean Institute, 2023)
Beach houses adorning the panorama of village community settlements above the sea waters of Wagom sub-district, Pariwari district, Fakfak Regency must be managed as residential areas whose people have productive behavior and business. The aim of the research is to find a strategy for economic empowerment of the sea village community, so that it develops into a micro industrial center area to encourage accelerated development of Fakfak district. Combined descriptive research using quantitative and qualitative analysis approaches. Data was obtained from closed direct interviews, using certain indicators compiled in the research questionnaire. The description of the questionnaire reflects the variables studied, and each answer is given a weighting value. Data was obtained through a conversion process and its validity was confirmed using a triangulation approach. The data is processed using SPSS statistics and also described using the SWOT approach to find the form of strategy. The research results show that the integration of livable houses requires planning the layout of the house in synergy with the conditions of the sea village; so that people can foster innovation and creativity in building businesses.